Red Eagles - Downing, David, 1946- (India Govt. of India, 1944)
World War II is nearly over. For the Russians the enemy is no longer Nazi Germany, but the American behemoth. At the Kremlin, Stalin's top man hatches a plan and five years later an atomic bomb is detonated within the borders of the Soviet Union. The Red Eagles traces the adventures of two spies sent to America to steal the greatest secret of all -- the key to producing the atomic bomb -- while hiding their true intentions from their compatriots.
Keywords: World War (1939-1945) -- Soviet Union -- Nuclear weapons